Improving the level of formalization of management processes at the main stages of electronic countermeasures against small unmanned aircraft systems to obtain conflict advantages - Kantsedal, V.M. (Radiotekhnika, 2025)
The possibilities are shown to achieve the RES complex conflict advantages in the dynamics of the conflict with a small unmanned system by rising its controllability as a result of improving the level of formalization of the processes for ensuring effectiveness at the main stages of its functioning. Along with the general features of the formalization of cycles within the stage-by-stage cognitive situational management of the REP complex, a number of its differences in the construction of control loops for individual stages are considered. They concern obtaining a high-quality information description of conflict situations when forming situational awareness, a well-founded choice of composition and optimization of the procedure for applying effective technical executive means of intelligence and various types of suppression in the contours of their management cycles. At the same time, a certain list of private performance characteristics and the values of their indicators, which are critically important for the UAS and the RES complex, is used as a systemic formalization tool for formalizing the description of conflict situations and management cycles for their resolution, which has certain features and relationships at individual stages. The formed list of indicators of key private performance characteristics objectively reflects the conditions and results of the use of means of observation and counteraction of the RES complex to small UAS at the main stages of its functioning. The sequence of their application comprehensively covers the main components that affect the quality of functioning of the corresponding means of the circuits of the cycles of the internal stage situational control of the RES complex. Increasing requirements for private performance characteristics, consistent with the vulnerabilities of UAVs, and restrictions on material resource costs and time shortages are sources of finding ways to effectively solve the problems of timely (early) detection of small UAVs and the phased implementation of various types of their suppression, which are increasingly strengthened, taking into account the specifics and tactics of using UAS.